(untitled) (Issues in Social and Environmental Accounting (ISEA), 2012)
When ISO 26000 published its first draft there were great expectations both inside the technical committee members and among the experts around the world that it would bring about drastic changes. This was mostly due to the world’s taste for such a coura geous effort. The amount of comments were so huge that the dates for issuing the draft at different stages of its progress were all delayed. It was in fact in part also due to some expected resistance on the part of those powers who were confronted with a pos sible great threat. Some definitions were going to be established as an international standard. Issues related to human rights, labour and environment have always been strongly defeated by some powers. The ever increasing attention worldwide shown by many comments sent to the committee in one side and the pressure to avoid a high level of social responsibility standard altogether led to a document existing now as the GUIDELINE for social responsibility instead of STANDARD. However it is a first step and to be optimistic one should say that it is perfectly ok for a start. One of the reasons, or better to say one of the remedies, for the powers to oppose to the creation of an international standard for corporate social responsibility is that a one size fits all approach to social responsibility is not applicable everywhere. It might be negated by emphasizing on the harmonized creature of human being, which is the real reason for any religion or human philosophy. A claim like this is equal to saying that as government in the world has its own way so they don’t need any instituted sets of rule to follow and every government can create its own. And the world which is going to grow to a globalised community is the best forum to reject this claim completely. Social responsibility is a matter of concern for human kind everywhere and in every aspect of their life consisting of technology and engineering, justice and law, labour and consumption and so on. To put it into a nutshell social responsibility is the disci pline and rule set of life: both career life and social life.